Analysis of the soil structure-interaction effects on the seismic vulnerability of mid-rise RC buildings in Lisbon. (April 2022) - Requena-Garcia-Cruz, M.V.; Bento, R.; Durand-Neyra, P.; Morales-Esteban, A.
Abstract: Soil-structure interaction (SSI) effects are usually omitted in the seismic vulnerability analyses of buildings. However, it has been proved that they might notably affect their seismic performance. In fact, European seismic codes establish that they should be included in the analyses of certain structures: with considerable second order ( p - Δ ) effects or mid/high-rise buildings. These characteristics are shared by reinforced concrete (RC) buildings in Portugal, which represent a considerable amount of its building stock. Moreover, a significant percentage (50%) have been constructed prior to restrictive seismic codes, i.e., without adequate seismic design. To obtain reliable results when including the SSI effects, the state-of-the-art reveals that a proper modelling of soil and foundations should be carried out. Nevertheless, most of the related studies are based on ideal structural and soil configurations. In addition, it has been found that there is a lack of studies and guidance, even in codes, on the quantification of the SSI effects. Therefore, this paper focuses on quantifying the SSI effects in RC buildings seismic vulnerability analyses by means of two approaches: the Beam on Nonlinear Winker method (BNWM) and the direct modelling of soil. The aim is to propose a method to practically include the SSI effects and to thoroughly characterise the soil behaviour. The method has been applied to a case study RC mid-rise building of Lisbon. A clay-type soil commonly found in Lisbon has been characterised, carrying the analyses out under undrained conditions. 3D finite elements procedures have been proposed to reproduce the complex soil nonlinear constitutive law to represent the behaviour of the entire system (soil + foundation + structure) as realistically as possible. The results have been compared in terms of the seismic safety verification and the fragility assessment. The results have shown that the modal behaviour and the deformed shape of the building are the same with and without the SSI. Nonetheless, it has been demonstrated that increasing the soil flexibility leads to higher periods and higher seismic damage. For this case study, the maximum capacity of the models can be reduced by up to 15% if the SSI effects are considered.